Inferior Frontal Regions Underlie the Perception of Phonetic Category Invariance. - Myers, Emily B.; Blumstein, Sheila E.; Walsh, Edward; Eliassen, James (Psychological Science., 2009)
A study examined neural sensitivity to acoustic changes within and between phonetic categories using a short-interval habituation paradigm. Functional magnetic resonance imaging of the region in the left inferior frontal sulcus revealed a pattern of activation consistent with phonetic invariance: insensitivity to acoustic changes within a phonetic category and responsiveness to changes between phonetic categories. In contrast, graded sensitivity to both within- and between-category changes was demonstrated by left superior temporal regions. Findings indicate that perceptual insensitivity to changes within a phonetic category may emerge from decision-related mechanisms in the left prefrontal cortex and contribute to an expanding body of literature suggesting that the inferior prefrontal cortex plays a domain-general part in the computation of category representations.